2019
DOI: 10.3746/pnf.2019.24.3.265
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Probiotic Lactobacillus and Bifidobacterium Strains on Memory and Learning Behavior, Long-Term Potentiation (LTP), and Some Biochemical Parameters in β-Amyloid-Induced Rat’s Model of Alzheimer’s Disease

Abstract: This study assessed the effects of probiotic supplementation on spatial learning and memory, long-term potentiation (LTP), paired-pulse facilitation (PPF) ratios, nitric oxide (NO) concentrations, and lipid profiles in a rat model of amyloid beta (Aβ)(1–42)-induced Alzheimer’s disease (AD). Forty rats were randomly divided into 4 groups. The sham (control and prevention) group received intracerebroventricular (ICV) injections of artificial cerebrospinal fluid, the Alzheimer group received ICV injection of Aβ(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…First reports indicate successful application in animal models: Lactobacillus plantarum, for example, was able to restore cognition and levels of acetylcholine esterase in the brain of a D-galactose-evoked AD-like rat model [94]. Similar results were obtained from investigations using genetic AD mouse models with Bifidobacterium breve strain A1 [95], SLAB51 (probiotic formulation, [96]) but also with Lactobacillus acidophilus, Lactobacillus fermentum, Bifidobacterium lactis, and Bifidobacterium longum in rodent sporadic AD models due to amyloid-β injection [97][98][99]. As only one explorative intervention study reports on a small cohort of AD human patients [100], the usefulness in humans is still not proven.…”
Section: Therapeutic Strategies Derived From Microbes Against Human Asupporting
confidence: 67%
“…First reports indicate successful application in animal models: Lactobacillus plantarum, for example, was able to restore cognition and levels of acetylcholine esterase in the brain of a D-galactose-evoked AD-like rat model [94]. Similar results were obtained from investigations using genetic AD mouse models with Bifidobacterium breve strain A1 [95], SLAB51 (probiotic formulation, [96]) but also with Lactobacillus acidophilus, Lactobacillus fermentum, Bifidobacterium lactis, and Bifidobacterium longum in rodent sporadic AD models due to amyloid-β injection [97][98][99]. As only one explorative intervention study reports on a small cohort of AD human patients [100], the usefulness in humans is still not proven.…”
Section: Therapeutic Strategies Derived From Microbes Against Human Asupporting
confidence: 67%
“…The probiotic treatment was also significantly improved the brain function in mice with AD model [ 165 ]. Razaeiasi et al [ 166 ]. have analyzed the effects of probiotics on spatial learning and memory and some other parameters in rats with AD.…”
Section: Interaction Of Gut and Nervous System: Gut–brain Axismentioning
confidence: 99%
“…Bifidobacterium longum 1714 substantially enhanced the learning and memory capabilities evaluated by fear conditioning test, novel object recognition task, and Barnes maze test ( Savignac et al, 2015 ). A mixture of probiotic bacteria enhanced amplitude of the potentiated responses recorded in the CA1 region of hippocampus in the normal reared rats ( Rezaeiasl et al, 2019 ).…”
Section: Probioticsmentioning
confidence: 99%
“… Beilharz et al (2018) showed that pre-exposure to a probiotic mixture (VSL#3) could prevent diet-induced memory spatial memory deficits in the rats introduced to the place task. In an animal model of AD, we showed that a cocktail of probiotics restored the impaired learning and memory in the beta amyloid (Aβ)-injected rats ( Rezaeiasl et al, 2019 ). In addition, in a series of experiments, we demonstrated that formulations of probiotics significantly improve the spatial memory examined by the Morris water maze in the ethanol treated ( Hadidi Zavareh et al, 2020 ), and the diabetic ( Davari et al, 2013 ), stressed ( Hadizadeh et al, 2019 ), and epileptic ( Bagheri et al, 2019 ; Tahmasebi et al, 2020 ) animal models.…”
Section: Probioticsmentioning
confidence: 99%
See 1 more Smart Citation